The Teachers’ Corrective Feedbacks on the Students’ Grammatical Errors in their Written Descriptive Text and Their Response. - Harianto Harianto; Ratna Dewi; Radiah Hamid (Institut Agama Islam Negeri Palopo, 2022)
This study aimed to find out (1) The teachers’ feedbacks on the students’ grammatical errors in the students’ descriptive text; (2) The students’ responses towards the teachers’ grammatical feedbacks in their descriptive text. The research design is Descriptive Qualitative Research conducted at SMP 1 Ma’rang Pangkep. The subject of research was three English teachers and thirty students who were selected by Purposive Sampling Technique. The instrument of data collected were teachers’ corrective feedback and the student’s response from the descriptive text. The result of the research showed that corrective feedback on the students’ grammatical errors in descriptive texts was more dominant in syntax errors, in this case mis formation errors. These errors occurred because of student’s mother tongue interference. The students still confused to choose the right word in a sentence because of the lack of knowledge or poor vocabularies and its used. Besides that, some students tried to translate the words one by one from Indonesian language into English without paying attention to the English structure rules. Students’ response by imitating the teacher's corrective feedback. Because they were aware that the parts which were given feedback were incorrect and they agreed with the correction suggested by the teacher. Thus, they directly imitated the corrections and did not change any other parts. And a few students ignore.